A Case of Severe Post‐Biopsy Bleeding and Perforation in Gastric Amyloidosis - Sho Matsuyama; Akihisa Fukuda; Go Yamakawa; Taro Ueo; Hiroshi Seno (JGH Open)
ABSTRACT We herein describe a case of severe post‐biopsy bleeding and perforation in gastric amyloidosis. A 70‐year‐old man who had been on dialysis underwent esophagogastroduodenoscopy and biopsy was performed. Post‐biopsy bleeding occurred, and three times of coagulation hemostasis and once clip hemostasis were performed. After the hemostasis, he eventually had a gastric perforation and omental patch surgery was performed, however, he passed away after the surgery. From the pathological finding of biopsy specimen, he was diagnosed with gastric amyloidosis caused by dialysis‐related amyloidosis. In patients of amyloidosis, the risk of bleeding and perforation is elevated due to vascular and tissue fragility. Therefore, when performing hemostasis in patients with gastrointestinal amyloidosis, clip hemostasis which minimizes tissue damage is considered preferable to coagulation hemostasis.